The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/adhm.202001632
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Iron–Boron Nanoparticles Designed for Neutron Capture Therapy Guided by Magnetic Resonance Imaging

Abstract: The combination of multiple functions in a single nanoparticle (NP) represents a key advantage of nanomedicine compared to traditional medical approaches. This is well represented by radiotherapy in which the dose of ionizing radiation should be calibrated on sensitizers biodistribution. Ideally, this is possible when the drug acts both as radiation enhancer and imaging contrast agent. Here, an easy, one‐step, laser‐assisted synthetic procedure is used to generate iron–boron (Fe–B) NPs featuring the set of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 79 publications
0
35
0
Order By: Relevance
“…A possible way to obtain multifunctional NPs is represented by bi-metallic NPs. In this context, Torresan et al [ 41 ] developed, by an easy, one-step, laser-assisted synthetic procedure, iron–boron (Fe–B) NPs coated with a shell of polyvinylpyrrolidone. The obtained NPs, exhibiting an average diameter of 26 ± 15 nm as measured by dynamic light scattering (DLS), featured the functions required for both neutron capture therapy (NCT) and MRI.…”
Section: Main Technological Strategies and Examples Of Imaging Agents Developed For Improving Diagnostic Efficiencymentioning
confidence: 99%
“…A possible way to obtain multifunctional NPs is represented by bi-metallic NPs. In this context, Torresan et al [ 41 ] developed, by an easy, one-step, laser-assisted synthetic procedure, iron–boron (Fe–B) NPs coated with a shell of polyvinylpyrrolidone. The obtained NPs, exhibiting an average diameter of 26 ± 15 nm as measured by dynamic light scattering (DLS), featured the functions required for both neutron capture therapy (NCT) and MRI.…”
Section: Main Technological Strategies and Examples Of Imaging Agents Developed For Improving Diagnostic Efficiencymentioning
confidence: 99%
“…In this sense, huge efforts are devoted to the development of new theranostic compounds for BNCT (e.g. Refs 25,26,35,38,39). One example is the halogenated (most of them iodinated) carborane derivatives that were shown to provide nuclear imaging by PET-CT (positron emission tomography-computed tomography, 124 I-, a positron emitter) and SPECT (single photon emission computed tomography, 125 I-, a gamma emitter) (Refs [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…), nanoparticles (e.g. Refs25, 26), boron cluster agents, carrier proteins conjugated with boron compounds (e.g. Refs27, 28) and bimodal drugs (with anti-tumoural and BNCT effects) such as metallocarboranes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we previously showed that techniques of femtosecond laser ablation and fragmentation can be used to fabricate stable solutions of low-size dispersed NPs of a variety of materials, including Au 28 , 31 , Si 32 , 34 , TiN 33 , 35 , elemental Bi 36 NPs. Recently, methods of laser ablation from a Fe-B alloy target were elaborated for the fabrication of composite Fe-B NPs 37 . The experiments were carried out in acetone in the presence of ligands (polyvinyl pyrrolidone, PVP) to control size characteristics and minimize oxidation effects, which could alter material stoichiometry.…”
Section: Introductionmentioning
confidence: 99%